Household Behavior in Choosing Travel Destinations: The Impact of Social Media and Digital Influencers - Oktaviani, Desy; Sumiyarti, Sumiyarti; Ratnawati, Nirdukita (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This study explores the influence of social media and digital influencers on household decision-making in selecting travel destinations, focusing on the mediating role of family perception. Using a quantitative approach, data were collected from 400 respondents through purposive sampling and analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). A structured questionnaire with a 1–5 Likert scale measured the impact of social media, digital influencers, family perception, and household decision-making. The findings reveal that social media does not significantly influence household decision-making, either directly or indirectly through family perception. Conversely, digital influencers have a notable impact, with family perception serving as a strong mediator. At a microeconomic level, credible content from influencers influences internal family discussions, while at a macroeconomic level, influencer collaborations enhance destination promotion, visibility, and local economic growth. This study offers insights into the strategic use of digital influencers for tourism promotion in West Java, providing valuable recommendations for local governments and tourism stakeholders to align marketing efforts with community preferences. The findings contribute to understanding the interplay between digital influencers, family perceptions, and household decisions, with implications for both tourism management and economic development.